Fracture fixation plates for fracture healing: comparing 316L stainless steel by metal injection molding technique plate with conventional plate in rabbit fracture model - Mohd Jan, Nurul Hafiza; Zulkifly, Ahmad Hafiz; Ibrahim, Mohd Zulfadzli; Omar, Mohd Afian; Abdul Jalil, Rosnani; Shaharudin, Aliah; Mat Nor, Rabiatul Adawiyah; Syed Mohamed, Syarifah Saffa 'Aina; Che Seman, Che Nor Zarida; Abdul Jalil, Normila (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2012)
Metal injection molding (MIM) combines the material flexibility of powder metallurgy and the design flexibility of plastic molding. With properties comparable, or better than, those of wrought steel, the MIM process are ideally suited to producing small and complex-shaped parts with outstanding mechanical properties. In addition to that, implants produced via this process have high final density and close porosity. This is an innovation to produce new orthopaedic fracture implants and it also can be used to device new special orthopaedic implants. The cost for the technique is cheaper when compared to the conventional technique. The objective is to evaluate the plate function in fracture using New Zealand White (NZW) rabbits. Evaluation was done at three, six, nine, twelve and twenty six weeks by using radiograph evaluation. The procedure commenced with pre-operation, intra-operative and post-operation sessions. There were three groups of experimental studies; Group O Sham group as control, Group 1; (fracture midshaft tibial implant with conventional plate by Synthes), Group 2; (fracture midshaft tibial implant with MIM plate). Both showed similar results as a method to hold the fracture fragments. X-Rays showed that callus formation occured in both groups (Conventional and MIM groups) of fracture site at three, six, nine and twelve weeks. Bridging was noted at six weeks. There is no infection noted in both groups with no adverse effects. Fracture union noted in all groups. These results revealed that MIM showed comparable function capabilities as the conventional plate to hold the fracture fragments and promote immobilization for fracture healing process.